Identification of a novel PAX6 mutation in a Chinese family with aniridia - Qiu, Jing-Jing (BMC Ophthalmol, 2019)
BACKGROUND: This study aims to investigate the clinical characterization and causative genetic defect of a four-generation Chinese family with autosomal dominant aniridia. METHODS: The recruited family members underwent comprehensive routine and ophthalmic examinations, and Sanger sequencing was performed to screen the mutation in PAX6. RESULTS: A novel heterozygous PAX6 deletion c.435_445delTAGCGAAAAGC (p.Ser146ThrfsX9) in exon 7 was identified in all affected individuals, but this was absent in any of the unaffected family members and in the 200 unrelated controls. CONCLUSION: A novel deletion in the PAX6 gene was identified in a Chinese family associated with aniridia, which expands the spectrum of the PAX6 mutation and its associated phenotype.